The Power of Brand Love: Unlocking Loyalty Through Image, Trust, and Satisfaction - Wijaya, Dody Hadi; Mansur, Amin (Research of Economics and Business, 2025)
This study evaluates the influence of Brand Image, Brand Trust, and Customer Satisfaction on Brand Loyalty, with Brand Love as a mediating variable. The research targeted Pantene Shampoo customers in the Kelapa Gading area, using questionnaires for data collection and multiple regression analysis for testing. Results show that Brand Image significantly affects Brand Love, while Brand Trust has a positive but insignificant effect. Customer Satisfaction, however, exerts a significant positive impact on Brand Love. In terms of Brand Loyalty, Brand Image has a positive yet insignificant effect, whereas both Brand Trust and Customer Satisfaction significantly strengthen loyalty. Brand Love itself also significantly enhances Brand Loyalty. Furthermore, Brand Image and Brand Trust have significant indirect effects on Brand Loyalty through Brand Love, while Customer Satisfaction does not demonstrate such an indirect effect. The managerial implications highlight the importance of strategies that go beyond functional value to build emotional connections with consumers. Companies should focus on strengthening Brand Love, as it plays a central mediating role. This can be achieved through consistent brand communication, maintaining product quality, and fostering authentic consumer engagement, all of which contribute to stronger and more sustainable loyalty.